Codoping Er‐N to Suppress Self‐Compensation Donors for Stable p‐Type Zinc Oxide. Issue 2 (16th November 2018) - Ouyang, Yifang; Meng, Zhisen; Mo, Xiaoming; Chen, Hongmei; Tao, Xiaoma; Peng, Qing; Du, Yong
Abstract: Stable p ‐type doping of zinc oxide (ZnO) is an unsolved but critical issue for ultraviolet optoelectronic applications despite extensive investigations. Here, an Er‐N codoping strategy for defect engineering of ZnO to suppress the self‐compensation of the donor‐type intrinsic point defects (IPDs) over the acceptor‐type ones is proposed. Via first‐principles calculations, the influence of nitrogen and erbium concentration on the stability of ZnO is investigated. The complex (ErZn ‐ m NO ) consisting of multiple substitutional N on O sites and one substitutional Er on Zn site is a crucial stabilizer. With an increase of the concentration of N, the absorption edges redshift to lower energy due to the impurity band broadening in the bandgap. The results suggest that codoping Er‐N into the ZnO matrix is a feasible way to manufacture stable p ‐type ZnO. Abstract : Stable p ‐type ZnO is important but challenging to achieve despite extensive efforts with single dopants or codopants. A first‐principles study reveals that the Er‐N codopant is stable, suppressing the self‐compensation of the donor‐type intrinsic point defects, with a strong infrared absorption when the N concentration is above 1.389%. The absorption edges redshift when N concentration increases.